Ammons Quick Test Validity among Randomly Selected Referrals. Issue 3 (December 2013) - Zagar, Robert John; Kovach, Joseph W.; Busch, Kenneth G.; Zablocki, Michael D.; Osnowitz, William; Neuhengen, Jonas; Liu, Yutong; Zagar, Agata Karolina
After selection using a random number table, from volunteer referrals, 89 Youth (61 boys, 28 girls; 48 African Americans, 2 Asian Americans, 27 Euro-Americans, 12 Hispanic Americans), and 147 Adults (107 men, 40 women; 11 African Americans, 6 Asian Americans, 124 Euro-Americans, 6 Hispanic Americans) were administered the Amnions Quick Test (QT). Means, confidence intervals, standard deviations, and Pearson product-moment correlations among tests were computed. The Amnions QT was moderately to strongly and significantly correlated statistically with: the Peabody Picture Vocabulary Test-3b (PPVT-3b); the Vineland Adaptive Behavior Scales-2 Parent/Teacher Form; the Wechsler Intelligence Scale for Children (WISC-4) or the Wechsler Adult Intelligence Scale (WAIS-4); and the Wide Range Achievement Test-Fourth Edition (WRAT-4) Blue and Green Forms. After 51 years, the original norms for the Amnions QT remain valid measures of receptive vocabulary, verbal intelligence, and auditory information processing useful to clinicians.